OPEN ACCESS TO SCIENTIFIC INFORMATION AS A FORM OF INFORMATION AND ANALYTICAL SUPPORT OF SCIENTIFIC ACTIVITIES AND COMMUNICATION - Havrilova, Liudmyla (Професіоналізм педагога: теоретичні й методичні аспекти, 2019)
The article analyzes the issue of open access to scientific information, which is currently being discussed in national and foreign studies (V. Bykov, N. Veretennikova, L. Holovko, S. Ivanova, N. Kunanets, L. Luparenko, O. Novitsky, O. Spirin, T. Yaroshenko, A. Yatsyshyn, D. Salo, L. Thomas, F. Manista, et al.). The relevance of the issue is associated with the massive publication of scientific research results in the network, the creation of electronic scientific repositories, and building a specific informational scientific environment. Interpretations of the concepts “open access”, “open educational resources” (OER), “open knowledge”, “electronic open access journal systems” are given. The advantages of using open access to scientific information, features of the “green” and “golden” ways are determined, as well as the electronic platforms that host Ukrainian scientific open access e-journals are analyzed, which constitute the purpose of the article. It is emphasized that the key factors in the emergence of the movement to open access are intensive informatization of society, the emergence and rapid spread of the Internet, as well as the relatively high and ever-increasing price of a subscription to scientific journals. As a result, at the beginning of the 21st century, several international documents appeared, they declared free online access to scientific literature and introduced the concept of open access. Examples of information projects and portals that provide open access to Ukrainian scientific sources: “Scientific periodicals of Ukraine at OJS”, “Science of Ukraine: Access to Knowledge” are given. It is noted that the legal framework for open access is provided by Creative Commons licenses. Examples of open electronic journaling systems used in national scientific institutions are given: Open Journal System (OJS), Joomla! The conclusions prove that awareness of the policy of open access to scientific information and the study of the work principles of the open access scientific electronic publications are important parts of the scientific activity of higher education institution teachers, employees of scientific institutions, doctoral students, and post-graduate students.